Impact of fermented wine lees on gut microbiota and metabolic responses in Guanling crossbred cattle - Mingming Zhu; Tiantian Zhang; Duhan Xu; Bijun Zhou; Kaigong Wang; Chaosheng Liao; Zhentao Cheng; Ping Li; Chao Chen (BMC Microbiology)
Abstract Background The addition of wine lees to diets can make up for the deficiencies caused by traditional forages in beef cattle farming. However, the effects of different wine lees ratios on average daily weight, gastrointestinal microbial community structure and metabolites in Guanling crossbred cattle have been rarely studied. This study assessed the effects of feeds containing wine lees on weight gain, gastrointestinal microbial community structure, and metabolites in Guanling crossbred cattle and elucidated the metabolic responses induced by wine lees. Eighteen cows were randomly assigned to receive fed concentrate (C group), feed containing 15% wine lees (group A), or feed containing 30% wine lees (group B) for 60 days. Results The average daily weight gain of group A and group B increased by 76.75% and 57.65%, respectively, compared with group C. Microbial community analysis showed that wine lees increased the abundance of Prevotella_1 in the rumen, decreased the abundance of Ruminococcaceae UCG 011 and Lachnospiraceae_FCS020_group in the rumen, and increased the abundance of Tyzzerella_4, Family_Xlll_AD3011_group, Granulicella, and Eisenbergiella in the cecum. Metabolomics analyses showed that wine lees decreased the concentrations of indole-3-ethanol in the rumen, and complexity cecal metabolism. Notably, linoleic acid metabolism was significantly enriched in both the rumen and cecum. Mantel test analyses indicated that the adverse effects of WL were reduced by stimulating the metabolism of linoleic acid, α-linolenic acid, and tryptophan, and these changes were mediated by intestinal microorganisms. The Guanling cattle cecum was enriched for several unfavorable metabolic pathways when wine lees concentrations reached 30%, which increased the likelihood of intestinal lesions. Conclusion This study shows that WL supplementation alters gut microbiota and metabolic pathways, improving cattle growth and health. Moderate WL levels (15%) enhance gut health and beneficial pathways (e.g., linoleic and alpha-linolenic acid metabolism). However, higher WL inclusion (30%) may activate adverse pathways, raising the risk of intestinal damage. To maximize benefits and minimize risks, WL levels should be carefully managed.